2008
DOI: 10.1094/phyto-98-8-0871
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Resistant and Susceptible Lettuce Cultivars by a Green Fluorescent Protein-Tagged Isolate of Verticillium dahliae

Abstract: Interactions between lettuce and a green fluorescent protein (GFP)-expressing, race 1 isolate of Verticillium dahliae, were studied to determine infection and colonization of lettuce cultivars resistant and susceptible to Verticillium wilt. The roots of lettuce seedlings were inoculated with a conidial suspension of the GFP-expressing isolate. Colonization was studied with the aid of laser scanning confocal and epi-fluorescence microscopes. Few differences in the initial infection and colonization of lateral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
110
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 42 publications
15
110
2
Order By: Relevance
“…Only a few hyphae could extend in a directed manner toward the xylem vessels where the rapid proliferation of the hyphae took place. These observations, together with the intercellular but not intracellular colonization, were consistent with the studies of V. dahliae on oilseed rape, lettuce and cotton roots (Eynck et al, 2007;Vallad and Subbarao, 2008;Zhang et al, 2012), which suggested that plant roots were able to impede the progress of V. dahliae hyphae within the cortical tissue either due to intercellular space blockage, active cellular defenses or a combination of both processes. Once the hyphae xylem vessel infection was established, it triggered a typical Verticillium resistance in the above-ground plant organs, even though it ultimately caused wilt disease as reported in a recent study (Yadeta et al, 2011).…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Only a few hyphae could extend in a directed manner toward the xylem vessels where the rapid proliferation of the hyphae took place. These observations, together with the intercellular but not intracellular colonization, were consistent with the studies of V. dahliae on oilseed rape, lettuce and cotton roots (Eynck et al, 2007;Vallad and Subbarao, 2008;Zhang et al, 2012), which suggested that plant roots were able to impede the progress of V. dahliae hyphae within the cortical tissue either due to intercellular space blockage, active cellular defenses or a combination of both processes. Once the hyphae xylem vessel infection was established, it triggered a typical Verticillium resistance in the above-ground plant organs, even though it ultimately caused wilt disease as reported in a recent study (Yadeta et al, 2011).…”
supporting
confidence: 88%
“…Once the hyphae xylem vessel infection was established, it triggered a typical Verticillium resistance in the above-ground plant organs, even though it ultimately caused wilt disease as reported in a recent study (Yadeta et al, 2011). In contrast with V. dahliae infection on lettuce roots, where the tips of the lateral roots were the first to invade vascular tissues (Vallad and Subbarao, 2008), we observed that colonies established on Arabidopsis and cotton root hair zones appeared to be the most successful, as they were the first to germinate, display hyphal growth and invade vascular tissues. Nevertheless, despite massive hyphae encompassing the root surface, only a few hyphae successfully invaded the root internal tissues.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Verticillium dahliae generally enters the cotton plant either by penetrating roots or via wounds in root tissues (Vallad and Subbarao 2008). After penetrating the cortex of the root, the fungus passes through the endodermis, invades the xylem vessels, eventually reaching the aerial parts of the plant (Tzima et al 2011).…”
Section: Introductionmentioning
confidence: 99%